Achtung – Panzer! - Quast, Julia (Indes)

Das Imaginäre der Plattformen: Soziale Medien als Infrastrukturen der Anerkennung - Schulz, Christian (Plattformforschung nach dem Digital Services Act – Interdisziplinäre Perspektiven)

Daten, Künstliche Intelligenz und Evidenz – neue Anforderungen an die Statistikausbildung an Hochschulen Data, artificial intelligence, and evidence—new requirements for statistics education at universities - Berger, Ursula; Biehler, Rolf; Binder, Karin; Elmer, Christina; Ertz, Florian; Hotz, Thomas; Huber, Sarah; Ickstadt, Katja; Kauermann, Göran; Küchenhoff, Helmut; Lübke, Karsten; Münnich, Ralf; et al. (AStA Wirtschafts- und Sozialstatistisches Archiv)
Zusammenfassung Das Positionspapier formuliert neun Thesen zur Weiterentwicklung der Statistikausbildung im Kontext von Data Science und Künstlicher Intelligenz. Im Zentrum stehen Data & Statistical Literacy, Datenqualität und -ethik, die Verbindung von Statistik und Machine Learning sowie die Stärkung einer eigenständigen Statistikdidaktik. Die Diskussionsbeiträge erweitern diese Perspektiven: Christina Elmer betont Wissenschaftskommunikation und AI Literacy, Helmut Küchenhoff projektbasiertes Lernen und Datenschutz, Christoph Weisser die industrielle Praxis und organisationsweite Datenkompetenz, Göran Kauermann die Verzahnung von Statistik und Data Science, und Rolf Biehler sowie Karin Binder die didaktische und institutionelle Weiterentwicklung. Die Replik greift diese Impulse auf und unterstreicht die interdisziplinäre Verantwortung für eine zukunftsfähige Statistikausbildung.

From Time-Saving to Skill-Building: Reframing Generative AI for Lesson-Planning—A Conceptual Design Paper - Vernholz, Mats; Sims, Craig; Treagust, David (Education Sciences)

AI has never been inherently interpretable: On a paradoxical origin of eXplainable AI (XAI) - Beer, Fabian; Schulz, Christian (RESET Journal (Recherches sciences sociale sur internet) Special Issue: Towards New Social and Historical Studies of Artificial Intelligence)

Initiating and establishing mathematical practices of determining and transforming numbers as a foundational skill in fostering mathematics teaching - Wiebe, Vivien; Häsel-Weide, Uta (Proceedings of the Nineteenth ERME Topic Conference: Connecting the Learning of Mathematics Teaching to Practice)

Securitization and Market Power – Evidence from European Banks - Herwald, Sarah; Uhde, André
Employing a unique hand-collected sample of 881 securitization transactions issued by 59 stock-listed banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically investigates if and how market power in the loan and deposit market may influence European banks’ incentives to engage in securitization activities. We construct product-specific residual Lerner Indices to measure market power in the loan and deposit market separately. Our results suggest that banks with higher loan and deposit market power securitize less, consistent with a reduced need for risk transfer and a reduced reliance on market-based funding. Various sensitivity analyses further show that these relationships vary across underlyings, issuance frequencies, and different time stages of securitization in Europe. Our findings contribute to the literature by disentangling loan and deposit market power as two further distinct determinants of securitization and thus, offer important insights regarding the ongoing policy debates on the consolidation of European banking markets and the revitalisation of the European securitization market.
Keywords: Securitization; market power; European banking

Planen. Bauen. Beteiligen. Bewegen. 16. Jahrestagung der dvs-Kommission „Sport und Raum“ vom 19.–20.09.2024 in Bad Driburg & Paderborn

Innovations- und Implementationsproblematik in der beruflichen Bildung – Studie zu Verständnissen und Prozessen im Kontext des InnoVET-Programms - Breuing, Friederike; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik – online)

Unternehmerische Finanzierungspolitik - Eine wertorientierte Einführung - Uhde, André; Paul, Stephan; Horsch, Andreas; Kaltofen, Daniel; Weiß, Gregor

A Comprehensive Grammar of Spoken and Written French as the First Fully Corpus-informed Grammar of French - Bürgel, Christoph; Siepmann, Dirk (Pedagogical Linguistics, Selected Papers from Constructionist Approaches to Language Pedagogy 4, 7:1, 17–3.)

Kinderspielplätze aus der Perspektive von Erwachsenen - Nutzungsverhalten, Attraktivitätskritieren und Implikationen für Beteiligungsverfahren - Kukuk, Marc; Meier, Heiko (Planen. Beteiligen. Bauen. Bewegen. 16. Jahrestagung der dvs-Kommission „Sport und Raum“ vom 19.–20.09.2024 in Bad Driburg & Paderborn)

Planen. Bauen. Beteiligen. Bewegen: Einführende Bemerkungen - Meier, Heiko; Kukuk, Marc; Sennefelder, Lisa (Planen. Beteiligen. Bauen. Bewegen. 16. Jahrestagung der dvs-Kommission „Sport und Raum“ vom 19.–20.09.2024 in Bad Driburg & Paderborn)

The Christian Right in Germany and the Alternative für Deutschland (AfD). Religious othering and group-focused enmity - Pinsch, Jan Christian (Religious Diversity and Global Concerns)

Construction of Polygons with Scratch and Computational Thinking - Stoppel, Hans-Jürgen

Explainable AI as a Rhetorical Technology: Promoting Civic Virtue in the Age of AI - Reijers, Wessel (Topoi)
Abstract Is explainable AI feasible and desirable, and are explanations of AI decisions always good? Many answer this question in the affirmative, but there is a growing discourse that is suspicious of the promises of explainable AI used to explain decisions towards users, considering it unfeasible, undesirable, and even potentially misleading. Could explainable AI be just a rhetorical foil? This paper proposes that, yes, explainable AI is a rhetorical technology but no, this does not necessarily make it undesirable. It starts by revisiting this debate according to the initial charge against rhetorics by Plato and Aristotle’s response, considering rhetoric pharmacologically, as not only a poison but also a cure for political life. It argues that, just as rhetoric was necessary to take care of the temporalities of public life, in court, the public event, and the assembly, so may explainable AI contribute to a rhetorical context. Yet, whether it does so is conditioned on the extent to which it cultivates the civic virtues relative to a respective context. The paper considers the examples of predictive policing, credit scoring, and prediction markets to argue about ideal states – civic virtues that may be cultivated in each appropriate context – and deviations that point at the risks of explainable AI to lead to domination, conformism, and political recalcitrance.

Polylogarithmic time algorithms for shortest path forests in programmable matter - Padalkin, Andreas; Scheideler, Christian (Distributed Computing)
Abstract In this paper, we study the computation of shortest paths within the geometric amoebot model , a commonly used model for programmable matter. Shortest paths are essential for various tasks and therefore have been heavily investigated in many different contexts. We consider the reconfigurable circuit extension of the model where the amoebot structure is able to interconnect amoebots by so-called circuits. These circuits permit the instantaneous transmission of simple signals between connected amoebots. We propose distributed algorithms for the shortest path forest problem where, given a set of k sources and a set of $$\ell $$ ℓ destinations, the amoebot structure has to compute a forest that connects each destination to its closest source on a shortest path. Our main results are two algorithms for hole-free structures. The first algorithm constructs a shortest path tree for a single source within $$O(\log \ell )$$ O ( log ℓ ) rounds, and the second algorithm a shortest path forest for an arbitrary number of sources within $$O(\log n \log ^2 k)$$ O ( log n log 2 k ) rounds. The former algorithm also provides an O (1) rounds solution for the single pair shortest path problem (SPSP) and an $$O(\log n)$$ O ( log n ) rounds solution for the single source shortest path problem (SSSP) since these problems are special cases of the considered problem. Then, we adapt the latter algorithm to an offset version of the problem. This allows us to solve the problem for amoebot structures with holes within $$O(h \log ^3 n)$$ O ( h log 3 n ) rounds w.h.p. where h denotes the number of holes.

Arbeitsplatz-KI: Zwölf Gestaltungsanker zur erfolgreichen Ko-Transformation von Mitarbeitenden, Prozessen & Strategie in der Finanzindustrie - Strich, Franz; Trang, Simon Thanh-Nam

Preferences for Taxing Wealth and Income - Maiterth, Ralf; Piper, Yuri; Schneider, Cornelius
We examine German individuals' preferences for income and wealth taxation and, importantly, the interplay between these two tax instruments. While prior research often examines wealth tax preferences in isolation, actual tax systems consist of multiple interacting taxes. To capture this dynamic, we elicit preferred tax burdens in a large-scale online experiment with 2,702 participants randomly assigned to one of four treatment groups: respondents state either an unspecified overall tax burden, separate income and wealth tax burdens, an income tax burden only, or a wealth tax burden only. Our baseline estimates reveal average (marginal) tax rates of approximately 17.4% (18.9%) for income and 4.1% (2.3%) for wealth. We find that participants associate wealth with an ability-to-pay taxes: when a wealth tax is not explicitly available, preferred income tax rates are approximately 30% higher. However, when both instruments are available, participants do not treat them as substitutes. Instead, they appear to treat the two taxes as separate mental bins: the standalone income and wealth tax burdens are combined in a notably additive manner, resulting in a significantly higher overall tax burden. Further, respondents apply implicit exemptions for low levels of wealth and favor a wealth tax base focused primarily on financial assets and real estate other than the primary residence.

Wie kommt der „grüne“ Strom in die Steckdose? – Eine multidimensionale Analyse der Vorstellungen von Grundschulkindern zu nachhaltiger Energienutzung - Kirsch, Alexander; Hellmich, Frank; Blumberg, Eva; Puppe, Ricardo (Vorstellungen von Kindern zu Themenfeldern der Nachhaltigkeit)